Coupling effect of PVDF molar mass and carboxyl content in CNTs on microstructure and thermal properties of CNT/PVDF composites. (15th June 2018) - Tian, Run; Zhang, Yanxia; Li, Zhipeng; Huan, Yangyang; Li, Guangfen; Li, Yi; Li, Wansheng
Abstract: Poly(vinylidene fluoride) (PVDF) membranes were blended with loading different kinds of carboxylated multi-walled carbon nanotubes (MWCNTs) by phase inversion method. PVDF with different molecular weight of 450 and 800 kDa was selected for our study, whereas four CNTs as pristine multi-walled carbon nanotubes, carboxylated multi-walled carbon nanotubes with different carboxyl content from 0.49, 2 to 3.86 wt.% were chosen for a comparison. The casting solution was set as 18 wt%. The effects of carboxyl content in MWCNTs and molecular weight of PVDF on membrane morphology, surface roughness, surface hydrophilicity, pore size and porosity were comprehensively investigated by field emission scanning electron microscope, atomic force microscopy, water contact angle measurements, the Brunauer–Emmett–Teller and the gravimetric method. The crystallinity, thermal and mechanical properties of different membranes were evaluated by x-ray diffractometer, differential scanning calorimetry and single-fiber electronic tensile tester. With the increase of carboxyl content in MWCNTs, the thermal stability of composite membranes was enhanced to some degree and the crystal transformation was slightly altered. The results indicated that the composite membranes containing carboxyl content of 0.49 wt.% in MWCNTs and higher molecular weight of PVDF possessed better mechanical properties, higher hydrophilicity and more preferable morphology, which have great significance in fundamental researches as well as the application of composite membranes.